ROLE OF ULTRASOUND IN ROTATOR CUFF TEARS: Ultrasound in Rotator Cuff Tears - Qayyum, Adil; Ilyas, Mohammad; Adil, Ruqqayia (Pakistan Armed Forces Medical Journal, 2009)
Objective: The objective of the study was to determine the role of ultrasound in rotator cuff tears and to calculate the sensitivity, specificity, positive & negative predictive values of ultrasonographic findings in Supraspinatus tears with magnetic resonance imaging (MRI). Study Design: Validation study. Place and Duration of Study: The study was conducted in the Radiology Department CMH Lahore, from April 2004 to October 2004. Patients and Methods: This study included 40 patients above 35 years of age who presented with shoulder pain and were referred for Ultrasound shoulder in Radiology Department. They were followed for their Magnetic Resonance Imaging (MRI) performed in Children Hospital ,  Defence National Hospital Lahore & Military Hospital Rawalpindi. Results: Out of 40 patients 17 patients were diagnosed as having rotator cuff tears on ultrasound while 23 patients were normal. When MRI was conducted in these patients, it showed 19 rotator cuff tears while 21 patients were normal. Out of 17 patients with cuff tears on Ultrasound, 10 showed full thickness tears while 7 had partial thickness tears. Out of 19 patients with cuff tears on MRI, 11 had full thickness tears and 8 had partial thickness tears.       Conclusion: Ultrasound should be the primary diagnostic method for shoulder pain and detection of rotator cuff tears because it is economical, noninvasive, quick and easy to perform. The MRI technique should be used secondarily because it provides more information about extent of tendons and has lower risk of artifacts.